Application of Digital Manuals with a Retinal Imaging Display in Manufacturing: Behavioral, Physiological, and Psychological Effects on Workers. Issue 2 (19th November 2012) - Nakanishi, Miwa; Sato, Tomohiro
Abstract This study analyses the behavioral, physiological, and psychological effects of digital manuals presented by a retinal imaging display (RID) on workers in the manufacturing industry. An RID consists of wearable glasses that enable users to view a digital image overlaying the real world. We conducted an experiment in which subjects assembled an object by referring to different types of manuals. The experimental results suggest that an RID enables users to conveniently examine real objects against information in the manual, reduces the information‐processing load while performing tasks, and supports effortless performance of tasks. However, using a monochrome picture manual with an RID increases the information‐processing load. On the other hand, a full‐color RID movie manual generates additional responses in users, such as psychological satisfaction.